Neoadjuvant Chemotherapy In Stadium Ib3, Iia2 And Iib Cervical Cancer - Winata, I Gde Sastra GdeSastra (Fakultas Kedokteran Universitas Andalas, 2023)
Aim: This study aimed to describe Paclitaxel-Carboplatin chemotherapy as neoadjuvant chemotherapy in stage IB3, IIA2 and IIB cervical cancer. Materials and Methods: The review was conducted by collecting journals from previous studies discussing neoadjuvant chemotherapy in cervical cancer stages IB3, IIA2, and IIB and in this case specifically discussing Paclitaxel-Carboplatin chemotherapy. Results: Neoadjuvan chemotherapy refers to systemic therapy intended to reduce the size of the tumor before the definitive operation. Several studies have shown that neoadjuvant chemotherapy has greater advantages than surgery alone for early stage cancers (IB3, IIA2, and IIB). Paclitaxel and Carboplatin are known chemotherapeutic agents that can be used as neoadjuvant chemotherapy. Conclusions: Neoadjuvant Chemotherapy regimen Paclitaxel Carboplatin is one of the options in performing therapy for early stage cervical cancer which can be very helpful in healing and cancer-free patient condition. Neoadjuvant chemotherapy followed by radical surgery has significant benefits that have been described in several previous studies. Clinical Significance: Neoadjuvant Chemotherapy regimen Paclitaxel Carboplatin may be used as therapy regimen for early stage cervical cancer with all advantage compared to only surgery. Thus, this type of regimen can be used to decrease mortality and morbidity in patient with stadium IB3, IIA2 and IIB cervical cancer.